Gossip in History - Trofimenkoff, Susan (Historical Papers / Communications historiques, 1985)
AbstractComment résumer un discours bilingue sur le commérage? What a task! The author dares to suggest that what really goes on at the annual meetings of the CHA is gossip. Que les historiens préfèrent V appeler "le parler boutique" indique leur malaise devant le commérage. And yet gossip, rich in information, evaluation and entertainment is much more descriptive of what historians actually do at the CHA. In order to explain the uneasiness surrounding the word gossip the author traces the origin and changing meanings of the word gossip /commérage. In both French and English the word follows an identical etymological course through history and somewhere around the sixteenth century, the word acquires the modern sense of a chattery woman. The author links this new meaning of the word to a series of other changes, associated with the Scientific Revolution of the same period, the results of which were the subordination of women. Gossip became a language of powerlessness. But it is also a language special to women, revealing a rich oral culture. Without quite knowing it, historians use aspects of that culture in their own work for they are constantly analyzing the changing norms of any given society. The author illustrates the importance of gossip for premodern societies but argues that as many illustrations can be found for the twentieth century, even in Canada. She concludes by suggesting that gossip may be the historian's clue to deciphering what was really going on in Canadian history which, for ease of reference, she divides into three chatty parts. Une histoire du commérage pourrait tout révéler. . ..